Interferon Regulatory Factor 6 (IRF6) Gene Variants and the Risk of Isolated Cleft Lip or Palate - Zucchero, Theresa M; Cooper, Margaret E; Maher, Brion S; Daack-Hirsch, Sandra; Nepomuceno, Buena; Ribeiro, Lucilene; Caprau, Diana; Christensen, Kaare; Suzuki, Yasushi; Machida, Junichiro; Natsume, Nagato; Yoshiura, Koh-Ichiro; et al. (The New England journal of medicine, 2004)
Cleft lip, cleft palate, or the combination of the two is a complex disorder caused by the interaction of several genes and possibly environmental factors. In this study, a variant of the gene encoding interferon regulatory factor 6 ( IRF6 ) confers a substantial risk of cleft lip or palate. A variant of the gene encoding interferon regulatory factor 6 ( IRF6 ) confers a substantial risk of cleft lip or palate. Birth defects arise from the interplay of multiple genetic and environmental factors. Although such complex traits are characterized by familial aggregation, recurrence rates within families are relatively low; the risk that an affected child will have a sibling who is also affected is typically less than 5 percent. Cleft lip, cleft palate, or the combination of the two is a common birth defect that varies in prevalence according to geographic origin, with populations of Asian and Amerindian ancestry having the highest rates and groups of African ancestry the lowest. 1 Isolated cleft lip or palate (i.e., a cleft occurring in the . . .